2011
DOI: 10.1103/physreva.83.042104
|View full text |Cite
|
Sign up to set email alerts
|

Strong correspondence principle for joint measurement of conjugate observables

Abstract: It is demonstrated that the statistics for a joint measurement of two conjugate variables in quantum mechanics are expressed through an equation identical to the classical one, provided that joint classical probabilities are replaced by Wigner functions and that the interaction between the system and the detectors is accounted for. This constitutes an extension of Ehrenfest's correspondence principle and is thereby dubbed the strong correspondence principle. Furthermore, it is proved that the detectors provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Equations (18) and (19), minus the contribution of the finite readout resolution, were already derived in Ref. [33]. We remark that there is a connection between the noises, due to the Kennard inequality, or better, to the canonically invariant generalization proved by Schrödinger [38] and Robertson [39].…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Equations (18) and (19), minus the contribution of the finite readout resolution, were already derived in Ref. [33]. We remark that there is a connection between the noises, due to the Kennard inequality, or better, to the canonically invariant generalization proved by Schrödinger [38] and Robertson [39].…”
mentioning
confidence: 83%
“…A rigorous proof, generalizing results presented in Refs. [33,34], that this is the correct formula will be provided elsewhere [35]. If no measurement of X was performed, thenK(−τ + 0) −K(−τ − 0) = 0, so that…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that this measurement is described by the probability distribution [45] W (x, p) = dx dp dγ…”
Section: Simultaneous Measurements Of Position and Momentummentioning
confidence: 99%
“…In doing so, we propose a generalization of the Moyal function [11]. The justification for this choice is that the Moyal function has revealed itself to be an extremely useful tool for describing the statistics of joint and sequential measurements of momentum and position [12,13].…”
mentioning
confidence: 99%